Progress in understanding middle Eocene nassellarian (Radiolaria, Polycystinea) diversity; new insights from the western equatorial Atlantic Ocean. (January 2023) - Meunier, Mathias; Danelian, Taniel
Abstract: Middle Eocene deep-sea sediment sequences cored at Ocean Drilling Program Site 1260 (Leg 207; equatorial Atlantic Ocean) yielded diverse and abundant radiolarian faunas that are conducive to biostratigraphic and palaeoceanographic research, as well as to the study of radiolarian diversity dynamics during this epoch of significant climate changes. However, many species present in these sediments still have not been formally described and are therefore neglected in most biodiversity surveys. In an effort to improve the taxonomic resolution of middle Eocene radiolarians, 15 new species of nassellarians are described and illustrated. The species are: Cymaetron ? dilatatus n. sp., Eucyrtidium levisaltatrix n. sp. (Eucyrtidiidae), Siphocampe pollen n. sp., Spirocyrtis ? renaudiei n. sp. (Artostrobiidae), Pterocyrtidium eep n. sp. (Rhopalosyringiidae), Petalospyris cometa n. sp., Petalospyris castanea n. sp. (Cephalospyrididae), Velicucullus armatus n. sp. (Theophormididae), Lychnocanium nimrodi n. sp. (Lithochytrididae), Aphetocyrtis zamenhofi n. sp., Aphetocyrtis ? columboi n. sp., Aphetocyrtis ? spheniscus n. sp. (Lophocyrtiidae), Albatrossidium regis n. sp., Albatrossidium annikasanfilippoae n. sp., and Phormocyrtis lazari n. sp. (Pterocorythidae). Stratigraphic range data are provided for each new species, as well as the orbitally tuned ages for their first and last occurrences. In addition to these new species, we also illustrate and document the stratigraphic distribution of four species described in early radiolarian studies and rarely reported since. UUID: http://zoobank.org/b5993e6b-659b-4220-80c2-c6ddccc13793